Bioremediation of Contaminated Soil with Hydrocarbons in Gas Stations with Alkane Hydroxylase Purified from Pseudomonas florescens - Mubarak, Hayfaa A.; Abd Alamer, Ammar A.; Hadi, Assel A.; Al-Salman, Ahmed; Q. Khaleel, Aaya Q. (Journal of Petroleum Research and Studies, 2025)
Petroleum product pollution of soil is a worldwide issue that threatens human and environmental health and destroys natural ecosystems. It also interferes with the ecosystem’s ability to function properly. Thus, the necessity to clean up polluted locations is vital. Bioremediation is an economical and ecologically friendly approach. The ability of certain bacteria to proliferate in situations contaminated with oil makes bacterial alkane hydroxylases highly desirable for bioremediation applications. Additionally, this enzyme facilitates specific hydroxylation of chemically inert alkanes, which is useful for synthesizing expensive compounds like medicines. In this study with a high level of alkane hydroxylase at 40°C after 72 hours of incubation, Pseudomonas fluorescens was found to be the most effective alkane degrader, followed by Pseudomonas aeruginosa, which had a lower productivity for alkane hydroxylase. Upon reaching a peak after 96 hours with 67% degradation of the hydrocarbons, alkane hydroxylase at a concentration of 150 µg/ml removed 43% of the hydrophobic pollutant from the polluted soil following a 24-hour incubation period.